Measuring gains in an EMP course and the perspectives of language and medical educators as assessors. (April 2016) - Wette, Rosemary; Hawken, Susan J.
Abstract: Significant numbers of international undergraduate medical students in English-medium universities find aspects of clinical communication skills challenging. The aim of this study was therefore to investigate the effectiveness of a course in English for medical purposes (EMP) to assist students to develop knowledge and skill in this area. The study also compared the perspectives of a language educator and a medical educator as assessors of role-play performance. Data were gathered from pre- and post-course tests of written knowledge and simulated medical interviews. Results from both test types indicated that students had made progress in their knowledge and ability to ask questions and respond appropriately. However, they had yet to develop skill in the more sophisticated aspects of interviewing such as maintaining rapport throughout the interview, using appropriate screening questions, and following a clear interview structure. Overall, the assessment judgements from the language and medical perspectives were in agreement; however, differences in the knowledge bases and interests of the two assessors led to some divergence. The study provides evidence of gains in knowledge and proficiency following a short ESP course of instruction, and of the value of the ESP teacher perspective in direct role-play assessments. Further studies are needed to corroborate these findings. Highlights: International undergraduate medical students participated in a short ESP (medical) course. Pre- and post-course written and roleplay tests measured knowledge and skill gains. Post-tests indicated good improvements in knowledge of vocabulary and language patterns. Gains in interviewing ability were clearly discernible, but more modest. The EMP teacher's assessments aligned with the medical educator across many criteria.